2020
DOI: 10.1038/s41598-020-59935-y
|View full text |Cite
|
Sign up to set email alerts
|

Palladium supported on polypyrrole/reduced graphene oxide nanoparticles for simultaneous biosensing application of ascorbic acid, dopamine, and uric acid

Abstract: In this study, we report a facile and effective production process of palladium nanoparticles supported on polypyrrole/reduced graphene oxide (rGo/pd@ppy nps). A novel electrochemical sensor was fabricated by incorporation of the prepared nps onto glassy carbon electrode (Gce) for the simultaneous detection of ascorbic acid (AA), dopamine (DA) and uric acid (UA). the electrodes modified with rGO/Pd@PPy NPs were well decorated on the GCE and exhibited superior catalytic activity and conductivity for the detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 37 publications
1
36
0
1
Order By: Relevance
“…Relative stability among the four epoxy-functionalized GO configurations ( Figure 1 a–d) was determined from comparing the per functional group in Table 1 . Our DFT calculation using the GGA-PBE functional with vdW-DF2 correction found that the stability of GO5-zigzag-B > GO5-para > GO5-zigzag-A > GO5-armchair was with a similar trend to the previous DFT study [ 20 ]. The most stable epoxy-functionalized GO, GO5-zigzag-B, was with an epoxy group at the opposite side of the graphene plane from the other four epoxy groups.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Relative stability among the four epoxy-functionalized GO configurations ( Figure 1 a–d) was determined from comparing the per functional group in Table 1 . Our DFT calculation using the GGA-PBE functional with vdW-DF2 correction found that the stability of GO5-zigzag-B > GO5-para > GO5-zigzag-A > GO5-armchair was with a similar trend to the previous DFT study [ 20 ]. The most stable epoxy-functionalized GO, GO5-zigzag-B, was with an epoxy group at the opposite side of the graphene plane from the other four epoxy groups.…”
Section: Resultssupporting
confidence: 82%
“…These made graphene an ideal material for developing biosensors. Many studies have reported electrode modification to improve the simultaneous determination of AA, DA, and UA in the CV and differential pulse voltammetry (DPV) experiments [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], e.g., the use of multilayer graphene nanoflake films (MGNFs) [ 10 ], graphitic sheets or multi-walled carbon nanotube/metal composites [ 11 , 13 , 14 , 17 , 18 , 19 , 20 , 21 ], and conducting polymers [ 12 , 15 , 16 , 22 ]. Moreover, electrical [ 23 ] and chemical [ 24 ] reduced graphene oxides (rGO) were also employed for AA/DA/UA detections due to the better conductivity than GO and their cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The nanocomposites were able to detect AA and UA in a co-existing system by using the separated redox peaks. Demirkan et al ( 2020 ) also detected AA and UA by preparing a novel electrochemical sensor, which was made by modifying palladium nanoparticles supported by polypyrrole/pd-reduced graphene oxide on glassy carbon electrode. Satisfactory results had been obtained when the sensor detected AA and UA in real urine samples in vivo, whether the concentration is high or not.…”
Section: Application Of Carbon Nanomaterials In Metabolic Disease Detmentioning
confidence: 99%
“…These made graphene an ideal material for developing biosensors. A number of studies have reported the electrode modification to improve the simultaneous determination of AA, DA, and UA in the CV and differential pulse voltammetry (DPV) experiments [9][10][11][12][13][14][15][16][17][18][19][20][21], e.g., the use of multilayer graphene nanoflake films (MGNFs) [9], graphitic sheets or multi-walled carbon nanotube/metal composites [10,12,13,[16][17][18][19][20], and conducting polymers [11,14,15,21]. Moreover, electrical [22] and chemical [23] reduced graphene oxide (rGO) were also employed for AA/DA/UA detections due to the better conductivity than GO and their cost effectiveness.…”
Section: Introductionmentioning
confidence: 99%